Knowledge and preventive practices of dengue fever among people attending tertiary care hospital - Thapa, Asha; Dhakal, Bijaya; Kumari Lamichhane, Rama; Regmi, Kamala (Journal of Chitwan Medical College, 2024)
Background: Dengue fever is a mosquito-borne viral disease that has rapidly spread and has frequent epidemic occurrences in many countries, including Nepal. Assessing people’s knowledge and preventive practices of dengue helps to prevent mosquito-related diseases. This study aimed to find out the dengue knowledge and preventive practices of the people attending a Tertiary care hospital.Method: A descriptive cross-sectional study was conducted at Bharatpur Hospital, Chitwan, from February to July 2023. Convenience sampling technique was used among the people who met the inclusion criteria. Ethical approval was obtained. The data were analyzed for knowledge and preventive practices, and association with socio-demographics. The SPSS version 20 was used for descriptive as well as inferential statistics. A p